1960
DOI: 10.1039/jr9600000983
|View full text |Cite
|
Sign up to set email alerts
|

205. Preparation of 3-substituted oxazolid-2,4-diones by cyclisation of N-substituted N-chloroacylcarbamates

Abstract: Substituted oxazolid-2,4-diones have been prepared from N-substituted carbarnates and a-chloroacyl chlorides. The intermediate N-substituted chloroacylcarbamates cyclise at higher temperatures t o t h e diones. The plots of t h e cyclisation rates of ethyl N-alkyl-N-chloroacetylcarbamates were straight, and steric effects influenced the cyclisation. Infrared spectra of t h e N-substituted chloroacylcarbamates and of 3-substituted oxazolid-2,4-diones are discussed.%SUBSTITUTED oxazolid-2,4-diones (111) are an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

1966
1966
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 0 publications
1
8
0
3
Order By: Relevance
“…L'absorption caractéristique du carbonyle de l'ester, trouvée à 5,9 y-pour l'uréthane, se présente à 5,6 ypour le dérivé. Ceci est qualitativement en accord avec les spectres de l'uréthane et du dérivé N-chloroacétylé publiés par d'autres auteurs (PIANKA et POLTON, 1960). En outre le dérivé possède une bande à 6,54 y-, absent pour l'uréthane, d'intensité presque égale à l'absorption du car¬ bonyle.…”
Section: Resultats Et Discussionunclassified
“…L'absorption caractéristique du carbonyle de l'ester, trouvée à 5,9 y-pour l'uréthane, se présente à 5,6 ypour le dérivé. Ceci est qualitativement en accord avec les spectres de l'uréthane et du dérivé N-chloroacétylé publiés par d'autres auteurs (PIANKA et POLTON, 1960). En outre le dérivé possède une bande à 6,54 y-, absent pour l'uréthane, d'intensité presque égale à l'absorption du car¬ bonyle.…”
Section: Resultats Et Discussionunclassified
“…Yields of the virtually pure (TLC, 1 H NMR) crude compounds are listed in Table 1; physical and spectral data are given below. 17, 55 (26), 43 (21), 41 (17).…”
Section: Procedures Cmentioning
confidence: 99%
“…We found that the solid product formed in this way could be EXPERIMENTAL 14 [l-C ] -Ethanol was supplied by The Radiochemical Centre, Amersham, U.K., and ethyl N-chloroacetyl-N-methylcarbamate (6) by Cheminova AS, Lemvig , Denmark.…”
Section: [L-c]-ethanol Was First Allowedmentioning
confidence: 99%